Gruppenaufnahme - Baumgarten
Innenminister Nordrhein-Westfalen Willi Weyer; Bundesinnenminister Werner Maihofer; Vorsitzender FDP-Landesverband Nordrhein-Westfalen Horst-Ludwig Riemer; Bundesaußenminister Hans-Dietrich Genscher;